الحقوق الشخصية في القرآن الكريم = Personal rights in al-Qurān al-Karīm - Ahmed, Farooq Omar; Elatrash, Radwan Jamal Yousef (IIUM Press, International Islamic University Malaysia, 2019)
This study aims at extracting and deducing the personal rights from the Noble Qur’an. Personal rights are related to the human being as a dignified creature. However, the researchers defined the word “Haqq” and how it is used by the Qur’an, which indicates many types of rights, such as the right to personal freedom, dignity, life, security, personal privacy, freedom of movement, protection of residence. The researchers utilized the inductive approach in order to extract the relevant Qur’anic ayat on the topic, and the analytical approach in order to discuss the relevant ayat on the topic, through consulting the opinions of the Mufassirin.